Self-rolled micro- and nanoarchitectures topological and geometrical effects - Fomin, Vladimir M. (De Gruyter, 2021)
The work shows the fascination of topology- and geometry-governed properties of self-rolled micro- and nanoarchitectures. The author provides an in-depth representation of the advanced theoretical and numerical models for analyzing key effects, which underlie engineering of transport, superconducting and optical properties of micro- and nanoarchitectures.